2019
DOI: 10.1177/0272684x19875022
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Social Factors Influencing Male Fertility in Nigeria

Abstract: Objectives Fertility level remains relatively high in Nigeria. Currently, it peaks at about six children per woman. Many studies have suggested targeting men in family planning programs to reduce fertility levels, particularly in patriarchal societies. Nigeria, being a patriarchal and multiethnic society, males’ influence on fertility behavior remains indisputable. Thus, this study explores contextual factors, such as sociocultural norms, beliefs, preferences, and perceptions, that influence male fertility beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In Nigeria, for example, where concern was comparatively high, there was comparatively little hesitation about having children (23% in Nigeria, 42% in Finland, for example). Scholars have linked the high fertility rates in Nigeria to strong patriarchal power structures [35] and a strong cultural stigma toward infertility [36], among other factors. Thus, the example of Nigeria shows how a complex set of factors affects the manifestations/impacts of climate anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, for example, where concern was comparatively high, there was comparatively little hesitation about having children (23% in Nigeria, 42% in Finland, for example). Scholars have linked the high fertility rates in Nigeria to strong patriarchal power structures [35] and a strong cultural stigma toward infertility [36], among other factors. Thus, the example of Nigeria shows how a complex set of factors affects the manifestations/impacts of climate anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a decrease in cash crops and agricultural yield reduces the economic value of children [ 37 – 40 ]. Importantly, in many studies respondents indicated that while they continue to desire a large number of children, they had come to the conclusion that this was ill-advised under current conditions [ 15 , 39 , 41 43 ]. As a respondent in Agadjanian’s (2005) study states, “Now it seems that people don’t want to have many children, but it is not so.…”
Section: Resultsmentioning
confidence: 99%
“…Another cultural and social norm that can influence fertility desires is gender/sex preference. In many communities, male offspring are more highly valued than female, and this preference has an effect on fertility desires, with extended childbearing in order to have male children a common practice [ 41 ]. Most studies (n = 32) found that persons who hold a sex preference have higher fertility desires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of infertility could be a devastating blow to Asian couples, and similar beliefs exist in African cultures. A study by Adewole and colleagues reported that men in many developing African societies view having children as a great achievement in their life (Adewole, Omotoso, & Asa, 2020). In contrast, people from European origins adhere more to individualism.…”
Section: Introductionmentioning
confidence: 99%